DISEMINASI TEKNOLOGI FERMENTASI UNTUK PERBAIKAN MUTU TEPUNG SAGU SERTA PENGENALAN PRODUK INOVASI TEPUNG MOSAS - Nurmiati Nurmiati; Periadnadi Periadnadi; Ika Thalia Nissa (Jurnal Hilirisasi IPTEKS, 2023)
Sago is one of the most potential carbohydrate-producing food crops to support food security programs in Indonesia. The Mentawai Islands have the largest potential for sago distribution in West Sumatra Province with the highest production rate reaching 469/ton, but the progress achieved has apparently not been sufficient to improve the physical quality of the sago flour produced, so the quality of Mentawai sago flour is considered not good enough. This activity aims to utilize fermentation technology to improve the quality of sago starch as well as the introduction of innovative MOSAS (Modified Sago Starch) flour products. This field activity carried out in South Siberut District involved lecturers and students (S1 and S2) Department of Biology-Unand. The activity was carried out in the form of a survey of sago processing home industry businesses followed by counseling on ways to improve the sago processing process. By microbiological fermentation or acidification on a laboratory scale, the quality of sago flour can be improved through the use of local microorganisms in physical changes, namely lightening the color of the flour. Efforts to advance microbiological approaches through potential acidifying microorganisms can also modify sago starch into MOSAS (Modified Sago Starch) products by increasing the swelling power and solubleness of sago starch. This can be an appropriate and easy solution that can be applied in small-scale/home-based sago starch management, in order to increase the quality and quantity of sago starch production. Choosing a production location and improving management conditions through sanitation and water sources in the extraction process is one of the most important quality improvement methods in determining the development of quality, clean Mentawai sago starch management in environmentally friendly production. Fermentation technology can be used as an effort to improve the quality of Mentawai sago.